O skrbi za zdravje delovnih volov na Slovenskem od 18. do konca 20. stoletja - Smerdel, Inja (Etnolog. Nova vrsta (Ljubljana), 2007)
The article presents the health care of working oxen, the indispensable working companions and highly appreciated assets of most Slovene peasants until the last quarter of the 20th century. The article's first part presents the relation between veterinary medicine and ethno-veterinary medicine, that is the state's efforts to prevent infectious diseases and its educational endeavours. The second part, based on sources, literature, and the author's own field research, presents a series of concise findings on healers, feeding,watering, harnessing, castration, shoeing, knowledge of harmful plants, identifying diseases, natural treatment, and the belief in the powers of saints and magic means.
Keywords: Slovenci; Slovenes; ethnology; etnologija; animal husbandry; živinoreja; govedoreja; voli; etnoveterina